The Effectiveness of Savings Programs in Shaping Students’ Financial Discipline in Islamic Boarding Schools - Mahmud Khoil Shofa Siagian; Uswah Hasanah (International Conference on Islamic Economic (ICIE), 2025)
Financial discipline is an essential life skill that enables individuals to manage resources wisely and prepare for future needs. In the context of Islamic boarding schools, or pesantren, this skill becomes even more important as students (santri) are expected to embody responsibility, independence, and adherence to Islamic values in daily life. Recognizing this need, An-Nikmah School Cooperatives introduced a sharia-based savings program, designed not only as a financial service but also as an educational initiative to instill long-term financial awareness and discipline. His study seeks to evaluate the effectiveness of the savings program in enhancing students’ financial discipline, to identify both supporting and inhibiting factors, and to assess the program’s contribution to the development of financial character consistent with Islamic principles. A descriptive qualitative method was employed, incorporating in-depth interviews, direct observation, and document analysis with cooperative managers and participating students. The findings reveal that the savings program contributes significantly to building systematic saving habits, encouraging accurate financial recording, and strengthening the integration of Islamic values in financial management. Despite these achievements, the program faces challenges such as limited financial literacy among students, inadequate access to technology-based recording tools, and insufficient training sessions to reinforce knowledge and practice. Overall, the study concludes that the sharia cooperative savings program at An-Nikmah School Cooperatives is effective in fostering disciplined, responsible, and independent financial behavior. Moreover, it provides a replicable model for financial education in Islamic boarding schools, offering valuable insights for policymakers, educators, and cooperative institutions in advancing financial literacy through faith-based initiatives.